Of mice and merchants: trade and growth in the Iron Age - Bakker, J; Rauch, F; Maurer, S (University of Oxford, 2018)
We study the causal connection between trade and development using one of the earliest massive trade expansions: the ?rst systematic crossing of open seas in the Mediterranean during the time of the Phoenicians. We construct a measure of connectedness along the shores of the sea. This connectivity varies with the shape of the coast, the location of islands, and the distance to the opposing shore. We relate connectedness to local growth, which we measure using the presence of archaeological sites in an area. We ?nd an association between better connected locations and archaeological sites during the Iron Age, at a time when sailors began to cross open water very routinely and on a big scale. We corroborate these ?ndings at the level of the world.